2017
DOI: 10.1002/chem.201605702
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole‐Linked Near‐Infrared Aza‐BODIPY Dyes as Triplet Sensitizers and Photoacoustic Contrast Agents for Deep‐Tissue Imaging

Abstract: Four new N-ethylcarbazole-linked aza-boron-dipyrromethene (aza-BODIPY) dyes (8 a,b and 9 a,b) were synthesized and characterized. The presence of the N-ethylcarbazole moiety shifts their absorption and fluorescence spectra to the near-infrared region, λ≈650-730 nm, of the electromagnetic spectrum. These dyes possess strong molar absorptivity in the range of 3-4×10 m cm with low fluorescence quantum yields. The triplet excited state and singlet oxygen generation of these dyes were enhanced upon iodination at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 64 publications
(20 reference statements)
1
57
0
Order By: Relevance
“…Figure 8p resents, for comparison, the structures, triplet state properties and singlet oxygen formation quantum yields of all halogenated aza-BODIPYs reportedu ntil 2017. [35,41,64,65] We demonstrated that the iodinated aza-BODIPYs 5-8,i n contrastt ot he non-iodinated counterparts 1-4,p roduce highly populated triplet state upon excitation, as evidenced by the observation of transient absorption spectra and lack of room-temperature emission from the singlet excited state (S 1 !S 0 ). In addition, iodinated aza-BODIPYs 5-8 efficiently harvest visible light, as evidenced by their relatively high molar absorption coefficients (e), viz.…”
Section: Discussionmentioning
confidence: 96%
“…Figure 8p resents, for comparison, the structures, triplet state properties and singlet oxygen formation quantum yields of all halogenated aza-BODIPYs reportedu ntil 2017. [35,41,64,65] We demonstrated that the iodinated aza-BODIPYs 5-8,i n contrastt ot he non-iodinated counterparts 1-4,p roduce highly populated triplet state upon excitation, as evidenced by the observation of transient absorption spectra and lack of room-temperature emission from the singlet excited state (S 1 !S 0 ). In addition, iodinated aza-BODIPYs 5-8 efficiently harvest visible light, as evidenced by their relatively high molar absorption coefficients (e), viz.…”
Section: Discussionmentioning
confidence: 96%
“…PAI contrast is dependent on optical absorption by molecules, which can be endogenous (blood, melanin or even water) or exogenous (organic dyes, nanoparticles, quantum dots, etc.) .…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41] The chalcones undergo nitromethanea ddition to give the nitro adduct, which, upon reaction with ammonium acetate to form the aza-dipyrromethene followed by complexation with BF 3 ·OEt 2 ,y ield the target aza-BODIPY dyes (Schemes S1-S2,see the Supporting Information). [36][37][38][39][40][41] The chalcones undergo nitromethanea ddition to give the nitro adduct, which, upon reaction with ammonium acetate to form the aza-dipyrromethene followed by complexation with BF 3 ·OEt 2 ,y ield the target aza-BODIPY dyes (Schemes S1-S2,see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the frequentlyu sed commerciallya vailable Ramanr eporters such as crystal violet (CV), malachite green isothiocyanate (MGITC), 4-mercaptobenzoic acid (4-MBA), Rhodamine 6G, and diethylthiatricarbocyanine (DTTC), there has been increased interest in the development of new Ramans ignature molecules for diversed iagnostic and imaging applications. [36][37][38] The synthetic flexibility of these dyes make them attractive for diversea pplications such as sensitizers for photooxygenation, photodynamic therapy,a sw ell as probesf or anions, cations, and neutralmolecules. [26][27][28] Despite the diverse attempts to discover new Raman reporter molecules, mosto ft he reported approaches suffer from several disadvantages such as low resolution, short wavelength absorption and high fluorescenceb ackground, which may mask the Raman signals.…”
Section: Introductionmentioning
confidence: 99%